Antibodies targeting Candida albicans Als3 and Hyr1 antigens protect neonatal mice from candidiasis - Singh, Shakti; Nabeela, Sunna; Barbarino, Ashley; Ibrahim, Ashraf S.; Uppuluri, Priya (Frontiers in Immunology, 2022)
Pre-term infants in neonatal intensive care units are vulnerable to fungal sepsis. In this population, Candida albicans remains the predominant fungal pathogen causing high morbidity and mortality, despite antifungal therapy. Thus, new preventative/therapeutic strategies against neonatal candidiasis are needed. Previously, we have reported that vaccination with recombinant forms of the C. albicans N-termini of the cell wall proteins Als3 (rAls3p-N) and Hyr1 (rHyr1p-N) protected adult mice from disseminated candidiasis. Further, in a Phase 1b/2a NDV-3A (an rAls3p-N formulated with alum) protected women from recurrent vulvovaginal candidiasis, with anti-Als3p IgG2 isotype being a biomarker for efficacy. Here, we performed a proof of concept study to evaluate if anti-Als3p or anti-Hyr1p antibodies are important for prevention of disseminated candidiasis in neonates. Als3 and Hyr1 antigens when adjuvanted with complete Freund’s adjuvant (CFA)/incomplete Freund’s adjuvant (IFA) induced a robust antibody response with a ten-fold higher titer of IgG2, than attained by either antigen formulated with alum. Transplacental transfer of these antibodies significantly reduced fungal burden in the kidneys of mice pups, and adoptive transfer of vaccinated mothers’ sera into pups displayed similar levels of protection. Neutrophils were found important for this efficacy. Finally, anti-Hyr1 antisera potentiated the activity of fluconazole in protecting from C. albicans infection. Our current studies are the first in the field to emphasize the importance of anti-Als3 and anti-Hyr1 antibodies in preventing neonatal candidiasis. Considering that Candida infections in low birthweight infants is a lethal infection, active and passive vaccination strategies using these antigens could have profound clinical relevance.